Dynamic mechanical analysis for quality evaluation of additively manufactured continuous fiber reinforced thermoplastic matrix composites subject to manufacturing defects - Rodriguez, Patrick A., author; Radford, Donald W., advisor; Ma, Kaka, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2019)
Continuous fiber reinforced polymers (CFRP) have become integral to modern mechanical design as value-added alternatives to metallic, ceramic and neat polymeric engineering materials. Despite the advantages of CFRP, current methods of preparing laminated continuous fiber reinforced polymers are fundamentally limiting in that reinforcement is typically applied only in the plane of the mold or tool. Additionally, key operations inherent to all CFRP processing approaches require a variety of skilled labor as well as costly net-shape, hard tooling. As such, additive manufacturing has risen to the forefront of manufacturing and processing research and development in the CFRP arena. Additive manufacture of continuous fiber reinforced thermoplastics (CFRTP) exhibits the potential to relieve many of the constraints placed on the current design and manufacturing of continuous fiber reinforced structures. At present, the additive manufacture of CFRTP has been demonstrated successfully to varying extents; however, comprehensive dialogue regarding manufacturing defects and quality of the processed continuous fiber reinforced thermoplastics has been missing from the field. Considering the preliminary nature of additive manufacture of CFRTP, exemplary processed composites are typically subject to various manufacturing defects, namely excessive void content in the thermoplastic matrix. Generally, quality evaluation of processed composites in the literature is limited to test methods that are largely influenced by the properties of the continuous fiber reinforcement, and as such, defects in the thermoplastic matrix are usually less-impactful on the results and overlooked. Hardware to facilitate additive manufacturing of CFRTP was developed and continuous fiber reinforced specimens, with high fiber volume fractions (~ 50 %), were successfully processed. Early efforts at evaluating the processed specimens using defect-sensitive Short-Beam Strength (SBS) analysis exhibited limited sensitivity to void content, coupled with destructive, inelastic failure modes. As a path forward, an expanded study of the effects of void content on the processed specimens was conducted by means of Dynamic Mechanical Analysis (DMA). Utilization of DMA allows for thermomechanical (i.e. highly matrix sensitive) evaluation of the composite specimens, specifically in terms of the measured elastic storage modulus (E'), viscous loss modulus (E"), damping factor (tan δ) and the glass transition temperature (Tg) of the processed composite specimens. The results of this work have shown that DMA exhibits increased sensitivity, as compared to SBS, to the presence of void content in the additively manufactured CFRTP specimens. Within the relevant range of void content, non-destructive specimen evaluation by DMA resulted in a measured, frequency dependent, 5.5 – 5.8 % decrease in elastic storage modulus per 1 % increase in void content by volume. Additionally, quality evaluation by DMA realized a marked decrease in the maximum measured loss modulus in the additively manufactured composites, ranging from 7.0 – 8.2 % per 1 % increase in void content by volume. Effects of void content were also measured in both the damping factor and glass transition temperature, where an approximate 1.6 °C drop in Tg was recorded over the relevant range of void content. The results of this work indicate, firstly, that DMA is a superior evaluation method, as compared to SBS, in terms of sensitivity to void content in additively manufactured CFRTP. Additionally, the results of this work provide a clear expansion of the current state of the literature regarding additive manufacture of CFRTP materials in that the effects of prominent manufacturing defects have been assessed with regard to thermomechanical material performance. Furthermore, and finally, the results of this work establish a direct path forward to characterize long-term effects of manufacturing defects, by means of DMA, on the creep-recovery and stress relaxation behavior of the relevant composite material system.
Keywords: composite materials; DMA; thermoplastics; continuous fiber reinforcement; additive manufacturing; dynamic mechanical analysis